2012
DOI: 10.3390/rs4010120
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Climate Effects on Vegetation in Northern Mixed Prairie Using NOAA AVHRR 1-km Time-Series NDVI Data

Abstract: Grasslands hold varied grazing capacity, provide multiple habitats for diverse wildlife, and are a key component of carbon stock. Research has indicated that grasslands are experiencing effects related to recent climate trends. Understanding how grasslands respond to climate variation thus is essential. However, it is difficult to separate the effects of climate variation from grazing. This study aims to document vegetation condition under climate variation in Grasslands National Park (GNP) of Canada, a grassl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…In the growing season (Figure 9a), vegetation growth was strongly dominated by temperature in most of the forest-covered (including EBF, ENF and DBF) southern China (26.5% of the research area) and by precipitation in grass-covered arid or semi-arid northern China (17.4% of research area). The study by Li and Guo [26] also found that precipitation has exerted more effects on NDVI than temperature in semi-arid grassland in Canada. A large portion (51.3%) of the research area was temperature-dominated in spring (Figure 9b), especially in northeastern and central China where the majority of vegetation is deciduous broadleaf forest (Figure 1).…”
Section: Relationships Between Ndvi and Multiple Climate Dirversmentioning
confidence: 98%
See 2 more Smart Citations
“…In the growing season (Figure 9a), vegetation growth was strongly dominated by temperature in most of the forest-covered (including EBF, ENF and DBF) southern China (26.5% of the research area) and by precipitation in grass-covered arid or semi-arid northern China (17.4% of research area). The study by Li and Guo [26] also found that precipitation has exerted more effects on NDVI than temperature in semi-arid grassland in Canada. A large portion (51.3%) of the research area was temperature-dominated in spring (Figure 9b), especially in northeastern and central China where the majority of vegetation is deciduous broadleaf forest (Figure 1).…”
Section: Relationships Between Ndvi and Multiple Climate Dirversmentioning
confidence: 98%
“…Seasonally, according to the detected abrupt change points (Figures S1f, S2f and S3f), it was mainly in summer and autumn when precipitation dropped. Though it is difficult to separate the effects of precipitation and grazing [26], the correlation and corresponding abrupt change points in NDVI and precipitation partly provide explanations for the decreasing NDVI in this area. Less precipitation limited the growth of grass or even partly destroyed the grassland ecosystem with low ecological resilience, and meanwhile rising temperature could have aggravated water limitation.…”
Section: Temporal Variation In Ndvi In Typical Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this NDVI data set is used as input to or for benchmarking global carbon, water and energy cycle models, it is important that we understand how much variability in vegetation growth is captured by this NDVI data set and if the causes of variability are linked to climate (precipitation, temperature, and solar radiation), disturbance (fires and large area outbreaks of pests), human management (e.g., irrigation and fertilization), or residual errors. Other studies have been published that reveal correlations between climate and NDVI [26][27][28][29][30], but none have combined analyses on monthly anomalies, lead time dynamics, cumulative climate effects and non-climate signal interference at global scales [31,32], and none have used global NDVI time series longer than 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of pasture, there is yet another important variable that must be taken into account: grazing. The distinction of the impact of each of these variables on the pasture can only be performed in controlled environments, where the history of grazing and precipitation is known [51,52].…”
Section: Regional Analysismentioning
confidence: 99%